Neighbourhood Development 2030: Protagonists, Key Factors and Future Trends—Results of a Delphi-Study - Schnur, Olaf; Markus, Ilka (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Demographic change coupled with fluctuating housing market regions in Germany will increasingly affect the mostly ignored meso level of neighbourhoods. In that context the two stage Delphi-study (2007/2008), titled „Demographic Impact in Urban Neighborhoods“, analyzes basic protagonists, key factors and future trends of neighbourhood development. The study includes fundamental questions like: Which neighbourhoods will be specifically affected by demographic impacts in the future? What are the strengths and weaknesses of certain neighbourhood types? How will neighbourhoods develop until 2030? What metatrends of neighbourhood development are recognizable? Which neighbourhoods have stronger chances of development: the homogeneously or heterogeneously age-structured ones?